Reduced Levels of Nitric Oxide Metabolites in Cerebrospinal Fluid Are Associated with Equine Protozoal Myeloencephalitis - Njoku, Chinedu J. (American Society for Microbiology, 2002)
Equine protozoal myeloencephalitis (EPM) is a disease of horses that is primarily associated with infection with the apicomplexan Sarcocystis neurona. Infection with this parasite alone is not sufficient to induce the disease, and the mechanism of neuropathogenesis associated with EPM has not been reported. Nitric oxide (NO) functions as a neurotransmitter, a vasodilator, and an immune effector and is produced in response to several parasitic protozoa. The purpose of this work was to determine if the concentration of NO metabolites (NO(x)(−)) in the cerebrospinal fluid (CSF) is correlated with the development of EPM. CSF NO(x)(−) levels were measured before and after transport-stressed, acclimated, or dexamethasone-treated horses (n = 3 per group) were experimentally infected with S. neurona sporocysts. CSF NO(x)(−) levels were also compared between horses that were diagnosed with EPM after natural infection with S. neurona and horses that did not have clinical signs of disease or that showed no evidence of infection with the parasite (n = 105). Among the experimentally infected animals, the mean CSF NO(x)(−) levels of the transport-stressed group, which had the most severe clinical signs, was reduced after infection, while these values were found to increase after infection in the remaining groups that had less severe signs of EPM. Under natural conditions, horses with EPM (n = 65) had a lower mean CSF NO(x)(−) concentration than clinically normal horses with antibodies (Abs) against S. neurona (n = 15) in CSF, and horses that developed ataxia (n = 81) had a significantly lower mean CSF NO(x)(−) concentration than horses that did not have neurologic signs (n = 24). In conclusion, lower CSF NO(x)(−) levels were associated with clinical EPM, suggesting that measurement of CSF NO(x)(−) levels could improve the accuracy of diagnostic tests that are based upon detection of S. neurona-specific Abs in CSF alone and that reduced NO levels could be causatively related to the development of EPM.